Deep vein thrombosis and pulmonary embolism: a prospective, observational study to evaluate diagnostic performance of the Tina-quant D-Dimer Gen.2 assay - Bertsch, Thomas; Behringer, Wilhelm; Blaschke, Sabine; Body, Richard; Davidson, Simon; Müller-Olling, Mirco; Guo, Ge; Rieger, Anna; Wahl, Annika; Horner, Daniel; Sun, Yuli; Turnes, Lucia; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: D-Dimer testing is a diagnostic tool for exclusion of deep vein thrombosis (DVT) and pulmonary embolism (PE). This study evaluated the diagnostic accuracy performance of the Tina-quant ® D-Dimer Gen.2 assay (Roche Diagnostics International Ltd, Rotkreuz, Switzerland) in patients with low/intermediate pre-test probability of DVT/PE using standard, age-, and clinical probability-adjusted cut-offs.In this prospective, observational, multicenter study (July 2017-August 2019), plasma samples were collected from hospital emergency departments and specialist referral centers. DVT/PE was diagnosed under hospital standard procedures and imaging protocols. A standard D-Dimer cut-off of 0.5 µg fibrinogen equivalent units (FEU)/mL was combined with the three-level Wells score; cut-offs adjusted for age (age  0.01 µg FEU/mL for patients >50 years) and clinical probability (1 µg FEU/mL for low probability) were also evaluated. An assay comparison was conducted in a subset of samples using the Tina-quant D-Dimer Gen.2 assay and the previously established routine laboratory assay, STA-Liatest D-Di Plus assay (Stago Deutschland GmbH, Düsseldorf, Germany).Results: 2,897 patients were enrolled; 2,516 completed the study (1,741 DVT cohort; 775 PE cohort). Clinical assessment plus D-Dimer testing using the standard cut-off resulted in 317 (DVT) and 230 (PE) false positives, and zero (DVT) and one (PE) false negatives. Negative predictive value (NPV) was 100.0% (95% confidence interval [CI]: 99.7-100.0%) and 99.8% (95% CI: 98.8-100.0%) for DVT and PE, respectively. After age-adjustment, NPV was 99.9% (95% CI: 99.6-100.0%) and 99.1% (95% CI: 97.8-99.7) for DVT and PE, respectively. False positive rates decreased (>50%) in clinical probability-adjusted analyses versus primary analysis. In the assay comparison, the performances of the two assays were comparable.The Tina-quant D-Dimer Gen.2 assay and standard D-Dimer cut-off level combined with the three-level Wells score accurately identified patients with a very low probability of DVT/PE.